Recovery of carbon fiber-reinforced polymer waste using dimethylacetamide base on the resin swelling principle - Li, Zixin; Xing, Mingfei; Zhao, Li; Li, Zhan; Wang, Yaping (Frontiers in Chemistry, 2022)
The mechanical recycling method of the carbon fiber-reinforced polymer (CFRP) has the advantages of simple process, less pollution and low cost, but only low utilization value of carbon fibers in powder or short fibers form can be obtained. To reduce the length and strength loss of the recycled carbon fibers, a novel and cost-effective dimethylacetamide (DMAC) swelling technique was developed to achieve rapid delamination of the CFRP laminates under mild conditions (120 °C–160 °C, 1 h). The corresponding swelling ratios and mass-loss rates of cured epoxy resin (CEP) were about 121.39%–157.39% and 0–0.69%, respectively. Excessive swelling of CEP in DMAC resulted in the cracking of the resin matrix between the adjacent carbon fiber layers. Thus the CFRP laminates were delaminated into soft single carbon fiber layers, which showed excellent cutting performance and reinforcing properties. The delamination products were cut into thin strips of different sizes and vacuum bag molded into new CFRP laminates. The flexural strength and tensile strength of the newly produced CFRP laminates were about 76.38%–90.98% and 94.61%–98.54% of the original CFRP laminates, respectively. More importantly, the chemical compositions of DMAC and CEP were unchanged during the physical swelling process. No organic pollutants (caused by resin degradation) were generated. And the used DMAC can be easily recycled by filtration. Therefore, this study provides a strategy for low-cost and high-valued recycling of CFRP waste.